Evaluasi Strategi Bersaing Maxi's Resto - Sabira, Zalvatania Salma; Hendrawan, Sanerya; Gunawan, Theresia; Gunawan, Agus (Economic Reviews Journal, 2024)
As time goes, many people have developed and ran businesses especially culinary businesses. Culinary businesses could be categorized as primary needs or for lifestyle needs. Since the coming of the Covid-19 pandemic made the decline in culinary businesses in Indonesia and it’s hard to hold on to them. One of the surviving restaurant that could survive until now is Maxi’s Resto which located in Bandung City. Maxi’s Resto is a restaurant that has a modern-european concept and located in the heart of Bandung City. Because of the geographical location, Maxi’s Resto has a lot of competitors that proves to be a challenge for the restaurant to be ahead from other restaurants. This research is done using internal analysis which is the Resource Based Theory to know the resources that the company has and the capability also external analysis which is the Porter Five Force to know how macro and micro environment can affect the company. Doing SWOT analysis to group up the factors internal and external of the company. Then IFE, EFE, and IE Matrix is used to count the final score of the processed data. According to the research, it was concluded that Maxi’s Resto has done some adaptive changes to adapt with the environment condition. Maxi’s Resto is still in the process of adaptation and trying to stabilize and recoup the losses that happened during the pandemic. Maxi’s Resto should be more active in the online marketing so they could reach more consumers. Seeing the resource factor that the company possesses, Maxi’s Resto has more prospect to grow very well and able to put itself in a favorable position in the industrial competition now if the company is able to manage their business well.